1991
DOI: 10.1080/01431169108929673
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Geosat altimeter and synthetic aperture radar measurements over east Greenland pack ice

Abstract: Altimetry over sea ice has attracted attention as a possible source of geophysical information. However, the interpretation of altimeter data records over ice has been hampered by a lack of high-resolution imagery for comparison. In this paper we compare Geosat altimeter data along a track over pack iceeast of Greenland with coincident synthetic aperture radar data obtained as part of the marginal ice zone experiment (MIZEX-87). Fuzzy-cluster analysis of altimeter pulse echo parameters delineates the marginal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Airborne measurements of the radar backscatter at 13.3 GHz made during March 1970 show the strongest returns at nadir (σ 0 = 15 dB) originating from open water within the pack ice, with backscatter decreasing from 6 to 0 dB as the ice thickness increased from 5 to 360 cm [ Parashar et al , 1974]. Comparisons of Seasat and Geosat altimetry with SAR revealed peaked waveforms with a backscatter of between 25 and 40 dB over new ice and leads [ Fetterer et al , 1991; Ulander , 1987]. By comparing Ku band airborne radar altimeter observations with coincident aerial photography, Drinkwater [1991] concluded that these strong peaked echoes originate from open water between ice floes.…”
Section: Radar Altimetry Over Sea Icementioning
confidence: 99%
“…Airborne measurements of the radar backscatter at 13.3 GHz made during March 1970 show the strongest returns at nadir (σ 0 = 15 dB) originating from open water within the pack ice, with backscatter decreasing from 6 to 0 dB as the ice thickness increased from 5 to 360 cm [ Parashar et al , 1974]. Comparisons of Seasat and Geosat altimetry with SAR revealed peaked waveforms with a backscatter of between 25 and 40 dB over new ice and leads [ Fetterer et al , 1991; Ulander , 1987]. By comparing Ku band airborne radar altimeter observations with coincident aerial photography, Drinkwater [1991] concluded that these strong peaked echoes originate from open water between ice floes.…”
Section: Radar Altimetry Over Sea Icementioning
confidence: 99%
“…Near-coincidental SAR imagery has proven a valuable source for verification of lead detection algorithms in altimeter data processing, e.g., [13,14]. In the late 1980s, two studies have been undertaken with data from Seasat and Geosat to relate SAR backscatter and altimetric data over sea ice, but both were limited to one SAR image as a reference [15,16]. Presently however, Copernicus' Sentinel-1 and Sentinel-3 two satellite constellations in addition to Radarsat-2/Radarsat-Constellation and CryoSat-2 provide an increasing and long term (Copernicus program) data availability especially at lower latitudes (below 81.5 • ).…”
Section: Introductionmentioning
confidence: 99%